First Report of Fusarium oxysporum Causing leaf spot on Basella rubra in Malaysia - Khoo, Ying Wei (Plant disease, 2022)
Basella rubra (family Basellaceae), locally known as 'Remayong Merah', is an edible perennial vine served as leafy greens in Malaysia. In May 2021, leaves with circular brown spots ranging from 3 to 10 mm wide with purple borders were found on B. rubra growing in Penampang (5°56'55.6"N 116°04'33.5"E), Sabah province. The disease severity was 80% with 10% disease incidence on 50 plants. As the disease developed, the lesions grew larger and they developed necrotic centers. Leaves with brown spot symptoms from five plants were collected from the field. Five leaf pieces (5 x 5 mm) were excised from lesion margins, surface sterilized based on Khoo et al. (2022b), before incubation on water agar at 25°C. When five pure cultures were obtained, the fungi were cultured on potato dextrose agar (PDA) at 25°C. After 5 days, fluffy white mycelia tinged with pink pigmentation showing on the underside of the colony were observed on PDA. Mycelia became violet in color as the culture aged. The isolates were incubated on carnation leaf agar at 25°C with a 12-hour light/dark photoperiod for 10 days. Sickle-shaped, thin-walled and delicate macroconidia (n= 30), predominantly 3 septate, ranging from 21.6 to 38.3 μm long by 2.7 to 4.2 μm wide in size were observed. Kidney-shaped, aseptate microconidia (n= 30) ranged from 6.2 to 11 μm long by 2.6 to 3.9 μm wide in size, and were formed on monophialides in false heads. Chlamydospores were detected both terminally and intercalarily, singly or in pairs, with smooth or rough walls. Genomic DNA was extracted from fresh mycelia of a representative isolate from Penampang based on Khoo et al. (2022a). The primers ITS1/ITS4 (White et al. 1990) and EF1/EF2 (O'Donnell et al. 1998) were used to amplify the internal transcribed spacer (ITS) rDNA and translation elongation factor 1-α (TEF1α) region, respectively based on PCR conditions as described previously (Khoo et al. 2022b). The products were sent to Apical Scientific Sdn. Bhd. for sequencing. In BLASTn analysis, ITS sequence (OK469301) was 99% (506/507 bp) identical to isolate TSE07 (MT481761) of Fusarium oxysporum, and the TEF1α sequence (OM743433) was 100% (705/705 bp) identical to isolate BLBL5 of Fusarium oxysporum. The TEF1α sequence of Penampang was analyzed at the Fusarium MLST site (https://fusarium.mycobank.org/), and had 98% similarity to TEF1α of F. oxysporum (NRRL 22551). The pathogen was identified as F. oxysporum based on morphological (Leslie and Summerell 2006) and molecular data. A volume of 0.16 ml of spore suspensions (1 × 106 conidia/ml) were inoculated on a spot on each leaf of every three healthy B. rubra seedlings at the two-leaf stage. An additional three B. rubra seedlings were mock inoculated by pipetting sterile distilled water on similar aged leaf. The seedlings were maintained in a greenhouse at 25°C with a relative humidity of 80 to 90%. Six days after inoculation, all inoculated leaves exhibited the same symptoms as observed in the field, while the controls showed no symptoms. The experiment was repeated two more times. The reisolated fungi had the same morphology and DNA sequences as the original isolate obtained from the field samples, completing Koch's postulates. F. oxysporum has been reported previously in Bangladesh and India causing leaf spot disease on B. rubra (Dhar et al. 2015; Shova et al. 2020). To our knowledge, this is the first report of F. oxysporum causing leaf spot on B. rubra in Malaysia. The identification of leaf spot caused by F. oxysporum will enable plant health authorities and farmers to identify practices to minimize disease on this important crop